Effect of Delayed Adjuvant Radiotherapy in Early Breast Cancer on Local Control, Distant Metastasis and Overall Survival: an Evidence Based Case Report - David Andi Wijaya; Agung Tri Cahyono; Aslim Taslim; Eka Indah Pratiwi; Fahmi Radityamurti; Fauzan Herdian; Ida Ayu Trisna Kumaladewi; Narissa Dewi Maulany; Tisa Prima Putri; Gregorius Ben Prajogi (Radioterapi & Onkologi Indonesia, 2017)
Breast cancer is the second most common cancer in the world and, by far, the most frequent cancer among women with an estimated 1,67 million new cancer diagnosed in 2012 (25% of all cancers). In principle, radiation therapy is indicated in early breast cancer after breast conserving surgery or after radical mastectomy-with-positive-or-near-margin. Unfortunately, not all aforementioned indicated patients could receive immediate treatment, often due to limited radiation therapy facility. We constructed this report to investigate comprehensively, whether delayed radiation therapy for indicated-post-surgical-early breast cancer case has a significant effect to survival (either locoregional or distant metastasis-free survival). Searching was conducted on PubMed®, Cochrane®, and Scopus®. After screening for titles and abstracts, we found 25 articles, 15 of which we finally included for performing full reading. From this systematic searching, we found that time to radiation is inconsistently related to locoregional survival, overall survival, and distant metastasis-free survival.